2012
DOI: 10.1017/s0007114512000098
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 and the risk of CVD in overweight and obese women: a randomised controlled trial

Abstract: Evidence indicates that vitamin D deficiency contributes to CVD. We investigated the effect of vitamin D 3 supplementation on cardiovascular risk factors in women. Healthy premenopausal overweight and obese women (n 77; mean age 38 (SD 8·1) years) were randomly allocated to the vitamin D (25 mg/d as cholecalciferol) or the placebo group in a double-blind manner for 12 weeks. Blood pressure, serum lipoproteins, apolipoproteins and anthropometric parameters were recorded. Dietary intake was recorded using 24 h f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 54 publications
(60 reference statements)
2
66
0
1
Order By: Relevance
“…27 However, other short-term studies of nonwhite populations found no effect of vitamin D on BP, although this could be a result of their low statistical power because of their small sample sizes (n≤100). 10,21,25 In summary, we have found that long-term vitamin D supplementation, which increased mean serum 25(OH)D concentrations >100 nmol/L for 18 months, had no effect on systolic or diastolic BP. These results, when combined with other studies that gave similarly high vitamin D doses for 12 months, indicate that high-dose long-term vitamin D supplementation does not lower BP in predominantly white, healthy adults without severe vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…27 However, other short-term studies of nonwhite populations found no effect of vitamin D on BP, although this could be a result of their low statistical power because of their small sample sizes (n≤100). 10,21,25 In summary, we have found that long-term vitamin D supplementation, which increased mean serum 25(OH)D concentrations >100 nmol/L for 18 months, had no effect on systolic or diastolic BP. These results, when combined with other studies that gave similarly high vitamin D doses for 12 months, indicate that high-dose long-term vitamin D supplementation does not lower BP in predominantly white, healthy adults without severe vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 74%
“…Most randomized controlled trials gave vitamin D for periods <1 year (most <6 months) [10][11][12][13][16][17][18][19][20][21][22][23][24][25][26][27] and, therefore, are of limited use for addressing the efficacy of long-term vitamin D supplementation in preventing and treating hypertension. Only 7 trials of long-term (≥1 year) supplementation have been Abstract-Previous randomized controlled trials of vitamin D supplementation and blood pressure (BP) mainly have given vitamin D for short periods (<6 months) or at low doses (400 IU per day).…”
Section: -15mentioning
confidence: 99%
“…In vitro experiments in rats have also shown that large doses of vitamin D 2 lead to increases in energy expenditure due to uncoupling of oxidative phosphorylation in adipose tissues [12]. However, randomized controlled trials (RCTs) testing the effect of vitamin D supplementation on weight loss in obese or overweight individuals have provided inconsistent findings [13][14][15]. It has also been suggested that obesity could result from an excessive adaptive winter response, and that the decline in vitamin D skin synthesis due to reduced sunlight exposure contributes to the tendency to increase fat mass during the colder periods of the year [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of CVD for 18 nmol/L was 2.2 (95% confidence interval, 1.7-2.7) compared with 1.0 (95% CI, 0.85-1.15) at 75 nmol/L. A study in Iran found that treating premenopausal overweight and obese women 1000 IU/day for 12 weeks resulted in significantly improved high-density lipoprotein-cholesterol, apoA-I concentrations and low-density lipoproteincholesterol:apoB-100 ratio (Salehpour et al, 2012). Serum 25(OH)D levels also impact proinflammatory cytokine levels.…”
mentioning
confidence: 98%